THE SCHOOL ENGLISH TEACHERS’ PERCEPTION ON ASSESSMENT TOWARD TEACHING PROGRAM AT UPT’S SPM LABORATORIUM PERCOBAAN BANDUNG - Hanafi Bilmona (Eltin Journal : Journal of English Language Teaching in Indonesia, 2013)
Assessment has recently become one of the new educational issues around Asia Pacific countries. The two reflective questions formulated are: 1) Is assessment new  in  the  educational  life  of  Indonesia?  2)  How  do  we  consider  our educational quality compared to countries around Asia pacific?  These questions urged this study to conduct a research in UPI’s SMP Laboratorium Percobaan Bandung to see the perceptions, planning and management of the school (the headmaster) and the three English teachers as the participants, in terms of their application of the assessment. In a qualitative descriptive method, the interviewing, observation and document analysis have been implemented to collect the data.. As a result, this school and the English teachers are only familiar  with  the summative assessment, part of assessment which is mainly grading or testing, evaluative, and less informative to identify students’ learning problem and to recommend teachers’ teaching modification and  improvement. KEYWORDS: assessment, teachers’ perception and the teaching